2002
DOI: 10.1103/physrevb.65.064422
|View full text |Cite
|
Sign up to set email alerts
|

Thermoremanence and zero-field-cooled/field-cooled magnetization study ofCox(SiO2)

Abstract: A systematic study of Co(SiO 2 ) granular films by means of transmission electron microscopy ͑TEM͒, dc and ac initial magnetic susceptibility, and thermoremanent magnetization ͑TRM͒ is presented. The experimental results are compared with simulations of zero-field-cooled ͑ZFC͒ and field-cooled ͑FC͒ magnetization and TRM curves obtained using a simple model of noninteracting nanoparticles. The simulated ZFC/FC curves, using the actual parameters obtained from the TEM images, show a different behavior than the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
153
2
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(176 citation statements)
references
References 26 publications
12
153
2
9
Order By: Relevance
“…To be more specific, Cr 2 O 3 generates Cr-based spinel-like nuclei which incorporate Fe thus creating a perfect base for further growth of magnetite crystallites (see Ref. [41] and therein references). Meanwhile, P 2 O 5 , which is a glass forming oxide, has a tendency to form phosphate complexes in borosilicate glass melts, like nonbridged Na-P species which are the critical nuclei (see Ref.…”
Section:  mentioning
confidence: 99%
“…To be more specific, Cr 2 O 3 generates Cr-based spinel-like nuclei which incorporate Fe thus creating a perfect base for further growth of magnetite crystallites (see Ref. [41] and therein references). Meanwhile, P 2 O 5 , which is a glass forming oxide, has a tendency to form phosphate complexes in borosilicate glass melts, like nonbridged Na-P species which are the critical nuclei (see Ref.…”
Section:  mentioning
confidence: 99%
“…17,20 It is shown that the ZFC and FC curves can be numerically obtained based on the thermal relaxation using a given size distribution and the anisotropy constant. 21 Shown in Fig. 2͑b͒ are the numerically calculated ZFC and FC curves using the size distribution and the anisotropy constant extracted from the ZFC curve in Fig.…”
Section: Shown Inmentioning
confidence: 99%
“…frozen ferrofluids [2], discontinuous metal-insulator multilayers (DMIMs) [8,13], co-sputtered metal-insulator films [14], selforganized particle arrays on surfaces [15], focused ionbeam structured thin films [16] and mechanically alloyed materials [17].…”
Section: Introductionmentioning
confidence: 99%